Resilience and vulnerability of post-ostomy patients with early-onset colorectal cancer from the perspective of social-ecological theory: a qualitative study - Fangfang Yang; Fangming Feng; Hongming Gu; Han Liang; Jin Zhang; Yusha Cheng; Weiying Zhang (Frontiers in Psychiatry)
BackgroundThe incidence rate of colorectal cancer (CRC) is rising among adults under the age of 50 (early-onset colorectal cancer, EOCRC). Post-ostomy dysfunction, along with negative perceptions due to incorrect public views and a decline in quality of life, has a significant impact on these individuals, their families, and social relationships.ObjectiveBy understanding the adaptation process of post-ostomy EOCRC(POEOCRC) patients, this study aims to provide information for developing targeted nursing interventions for this population.MethodsBased on the social-ecological theory, semi-structured, in-depth interviews were conducted with 16 POEOCRC patients in China between May 2023 and January 2024.Colaizzi’s method of phenomenology was employed for data analysis.ResultsThis study found two aspects of adaptation experience in POEOCRC patients. For resilience, three themes emerged:(1) Micro-Positive individual psychological experiences, (2) Meso-Positive adjustment within the family and (3) Macro-Social resource integration and utilization. In terms of vulnerability, three themes were as follows:(1) Micro-Persistent negative experiences, (2) Meso-Family crisis caused by the ostomy and (3) Macro-Urgency and fragility of social support.ConclusionThis study based on the social-ecological theory and highlights different dimensions of resilience and vulnerability experienced by POEOCRC patients. Early and targeted interventions to promote patients’ coping skills and their ability to adapt to family and society.